In multiple situational light settings, visual observation for skin colour assessment is comparable with colorimeter measurement - Wright, C. Y.; Wilkes, M.; du Plessis, J. L.; Reeder, A. I.; Albers, P. N. (Skin research and technology, 2016)
Background Finding inexpensive and reliable techniques for assessing skin colour is important, given that it is related to several adverse human health outcomes. Visual observation is considered a subjective approach assessment and, even when made by trained assessor, concern has been raised about the need for controlled lighting in the study venue. The aim of this study is to determine whether visual skin colour assessments correlate with objective skin colour measurements in study venues with different lighting types and configurations. Methods Two trained investigators, with confirmed visual acuity, visually classified the inner, upper arm skin colour of 556 adults using Munsell® colour classifications converted to Individual Typology Angle (°ITA) values based on published data. Skin colour at the same anatomic site was also measured using a colorimeter. Each participant was assessed in one of 10 different buildings, each with a different study day. Munsell®‐derived °ITA values were compared to colorimeter °ITA values for the full sample and by building/day. Results We found a strong positive, monotonic correlation between Munsell® derived °ITA values and colorimeter °ITA values for all participants (Spearman ρ = 0.8585, P < 0.001). Similar relationships were found when Munsell® and colorimeter °ITA values were compared for participants assessed in the same building for all 10 buildings (Spearman ρ values ranged from 0.797 to 0.934, all correlations were statistically significant at P < 0.001). Conclusion It is possible to visually assess individual skin colour in multiple situational lighting settings and retrieve results that are comparable with objective measurements of skin colour. This was true for individuals of varying population groups and skin pigmentation.